A study to investigate the dynamic loan-loss provisioning method adopted by the Spanish banking system and the implications for the Spanish economy during the global financial crisis. - Linton, Thomas (2013)
The recent global financial crisis has proven that procyclicality of loan loss provisions is an increasingly important issue, as banks underestimate credit risk and lower credit standards in good times, leading to under-provisioning and the need subsequent large increases in provisions in bad times. The issue of moral hazard exists within developed economies and throughout the global financial system, where central banks and state governments are known to be the ‘lender-of-last-resort’ for banks deemed globally systemically important financial institutions. This joint issue means that banks’ risk management processes, principally managing their credit risk, solvency and minimum capital requirements is of increasing importance to financial supervisors and regulators.